Peran Dinas Sosial Dalam Menangani Kemiskinan di Kecamatan Medan Helvetia - Daulay, Siti Khairunnisa (KESKAP: Jurnal Kesejahteraan Sosial, Komunikasi dan Administrasi Publik, 2024)
This research is motivated by the important role of social services in dealing with poverty in Medan Helvetia District. Currently, poverty is a major problem in Medan City, especially in Medan Helvetia District, where overcoming it needs to be done seriously, creatively and continuously. If it is not paid attention to, the social problems in Medan Helvetia District will never be resolved in the communities affected. This research aims to find out the role of the Social Service in dealing with poverty in Medan Helvetia District. The research method used is a qualitative descriptive research method. The data collection techniques used in this research are observation, interviews and documentation. In this research, the data analysis technique used by researchers is qualitative analysis techniques. From the research that has been carried out, the result of this research is the importance of the role of the Social Service in Handling Poverty in Medan Helvetia District. Handling poverty is an important thing that must be done immediately by the government. This is because poverty will give rise to other problems such as crime and disease